Using standards to improve teaching and learning : improving curriculum and assessment. - ASCD (Alexandria, Va : Association for Supervision and Curriculum Development, 2000)
Library has"
Facilitator's guide, Tapes 1,2,3.
Keywords: Curriculum planning (Standards-based education)) -- United States; Effective teaching -- United States; Education -- Standards -- United States